OTHR-30. Multidisciplinary approach to childhood cancer bio-banking improves enrollment and enables better access to diagnostic and therapeutic studies. (3rd June 2022) - Zhukova, Nataliya; Habarakada, Dilru; Drinkwater, Caroline; Danks, Andrew; Xenos, Chris; Kumar, Beena; Haddad, Lauren; Wood, Paul; Cain, Jason; Firestein, Ron; Downie, Peter
Abstract: Despite the significant progress made in the multi-modal treatment of childhood malignancies over the last four decades with a concomitantly increased cure rates, the benefit is still largely limited to patients with leukemias, lymphomas and localized non-CNS solid tumors, leaving patients with high-risk non-CNS solid tumours and most CNS malignancies with minimal advancements. More research is critical to understand what drives these cancers and to investigate the best ways to deliver curative therapies. Translational research relies on patient-derived tissue samples, animal models and cell-cultures to understand the biological, genetic, and molecular mechanisms of disease. To facilitate patient care and outcomes, it is becoming increasingly important that paediatric clinical trials include tissue availability as part of eligibility criteria, making collection and storage of patient tissue a mandate of personalised medicine and a pillar of modern paediatric cancer medicine. Monash Children's Cancer Biobank was established in 2011. Since 2017, a total of 64 patients were diagnosed with CNS malignancies across all grades, with an overall 69% of patients' tissues being biobanked at the time of initial diagnosis. A co-ordinated, multidisciplinary approach to biobanking is crucial to the success of tissue acquisition. Through the combination of an educational forum, regular neuro-surgical multi-disciplinary meetings, and the early involvement of medical oncology and biobank staff, with our neurosurgical and clinical pathology colleagues, as part of patient management planning, the tissue acquisition for biobanking increased from 44% to 82% over the course of 5 years. This consequently led to a 100% enrolment to tissue-enabling studies, significantly improving identification of targetable molecular lesions, enrolment onto treatment clinical trials and identification of patients with cancer predisposition syndromes.